The Role of Desmopressin in the Management of Severe, Hypovolemic Hyponatremia: A Single-Center, Comparative Analysis. Issue 1 (20th March 2018) - Ward, Frank L.; Tobe, Sheldon W.; Naimark, David M. J.
Background: The role of desmopressin (DDAVP) to prevent or treat rapid serum sodium concentration ([Na]s) correction during hyponatremia management remains unclear. Objective: To assess DDAVP use during the first 48 hours of severe, hypovolemic hyponatremia management. The primary study hypothesis was that the use of DDAVP would slow the rate of [Na]s correction compared with those not receiving DDAVP. Design: A retrospective, observational, comparison study. Setting: A single, Canadian, tertiary center. Patients: All admitted patients referred to the nephrology service for severe, hypovolemic hyponatremia ([Na]s < 125 mmol/L) over a 12-month period from November 2015. Measurements: The primary outcomes measure was the [Na]s after medical management for 48 hours. The length of hospital stay was also measured. Methods: Patients were grouped based on whether they received DDAVP during the first 48 hours of treatment, and [Na]s correction was compared between groups using linear regression. An exploratory, multivariable, linear regression model was used to adjust for diabetes status, active malignancy, intensive care unit (ICU) admission, and hypertonic saline administration. Results: Twenty-eight patients were identified, with baseline mean [Na]s of 112.7 ± 6.6 mmol/L versus 117 ± 4.3mmol/L ( P = .06) in those receiving (n = 16) and not receiving DDAVP (n = 12), respectively. The DDAVP group had a more rapid [Na]s correction on the first day compared with those not receiving DDAVP, 7.7 ± 3.8 mmol/L/d versus 5.1 ± 2.0 mmol/L/d ( P = .04). On the second day, there was a similar rate of [Na]s correction between groups: 1.3 ± 4.3 mmol/L/d versus 2.6 ± 3.2 mmol/L/d ( P = .39), respectively. Overall, there was no difference in [Na]s correction after 48 hours between those who received DDAVP and those who did not: 121.7 ± 7.5 mmol/L versus 124.8 ± 5.7 mmol/L ( P = .24). Patients who had experienced an overcorrection were successfully treated with DDAVP (n = 5), so that no patient had an ongoing overcorrection by 48 hours. Limitations: The limited sample size and lack of randomization preclude definitive conclusion on the additional benefit of DDAVP to standard care. Conclusion: DDAVP appears to be safe and effective in the management of severe, hypovolemic hyponatremia, associated with similar [Na]s correction to those who did not receive DDAVP after 48 hours, despite an initial more rapid correction. A randomized trial should examine what benefit DDAVP confers in addition to standard care in the management of severe, hypovolemic hyponatremia.